The Impact of Tourism on Coastal Communities on Small Islands: Case on Pari Island, Seribu Islands Regency - Triyono Triyono; Vera Bararah Barid; Nurul D. M. Sjafrie; Budhi Gunawan; Yudi Nurul Ihsan; Herry Yogaswara (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
Marine and coastal tourism in the small islands is one of the fastest-groing trourist activiities compared to the other tourism activities. However, along with the explosive growth of tourism activity, tourism has a potential impact on the small island; hence, the sustainability of tourism itself is questionable. This research was conducted in July-August 2021 on Pari Island, Seribu Islands Regency. This study aims to determine the impact of tourism development on the people's lives on Pari Island from the economic, socio-cultural, and political dimensions. The data were collected through a questionnaire with 317 respondents who were the head of the family; therefore, the data will analyze descriptively. The impact of tourism from the economic dimension is the development of livelihoods, reduced unemployment, improved quality of life, increased wages and income levels, despite an increase in the cost of living happened. From the socio-cultural dimension, there are limited residential areas for people who have moved to and from Pari Island. Then, it is known that tourism does not influence the local community's cultural changes. Meanwhile, from the political dimension, the community has been included in making decisions regarding tourism on this island.